How Pious People Live from the Viewpoint of Holy Quran - Yekan, Raziyeh Sabour Dizaj; Rad, Firouz (Journal of History Culture and Art Research, 2017)
This study examines the life of pious people according to the viewpoint of Quran by implementing a descriptive approach. The Quran is detailed to extract related verses regarding behaviors of pious people in different social, economical, political, family related as well as religious issues. The results suggest that the regular foundation of the pious people's lifestyle is rooted from the Divinity beliefs. The worship and morality dimensions of the religion through the inspirational books have been determined in order to reach and access to these beliefs.